Tuberculosis and HIV mortality in Russia - E. B. Tsybikovа; I. M. Son; A. V. Vlаdimirov (Туберкулез и болезни лёгких)
The objective: to study changes in the structure of mortality from tuberculosis and HIV infection in Russia from 2000 to 2017.Subjects and methods. The data of the Federal State Statistics Service on the mortality of the Russian population from tuberculosis and HIV infection (standardized ratio per 100,000 population) for 2000-2017 were studied. Data on the structure of patients with TB/HIV co-infection were obtained from Form no. 61 of the federal statistical monitoring for 2017.Results. In Russia, there has been a steady decrease in the mortality rate from tuberculosis, the value of which in 2017 reached 5.9 per 100,000 people. At the same time, the average values of the mortality rate from tuberculosis have shifted towards the older age groups reaching maximum values in the age group of 45 years and older. On the contrary, the analysis of mortality from HIV infection (2006-2017) detected its unprecedented increase from 1.6 to 12.6 per 100,000 population. The maximum concentration of mortality from HIV infection was observed in young age groups (35-44 years old). The increase in mortality from HIV infection was accompanied by a change in the structure of mortality from infectious diseases: the proportion of tuberculosis decreased from 79.1% (2000) to 27.4% (2017), and the proportion of HIV infection increased from 0.1% ( 2000) to 57.2% (2017). Currently, in Russia, mortality from HIV infection in young age groups has taken a leading position in the structure of causes of death from infectious diseases, displacing mortality from tuberculosis.